Vesicular Lithlasis: are there cases in which intraoperative cholangiography may be obviated? - González, Jorge; di Donna, Bruno; Colet, Andrés; Domínguez, Juan; Estefan, Alberto (Cirugía del Uruguay, 1984)
Retrospective study of a series of 81 cholecystectomized patients, also subjec to intraoperative cholangiography and exhibiting the following requisítes: single or multiple vesicular llthiasis, with gallstones more than 3 cm in diameter, fine cystic canal, no galls• tones in C.B.D. palpation, hepato-choledocho no larger than 7 mm and absence of pancreatitis. In none of them the intraoperative cholangiography lndicated lithlasis of C.B.D. neither pathology and/or biliary associated anomalies having a surgical meanlng.